Metrological Analysis of Sphericity Geometry to Lathe Conditions at the Mechanical Technology Laboratory of the Department of Mechanical Engineering Politeknik Negeri Pontianak - Karyadi, Edi; Rusadi, Rusadi; Hadimi, Hadimi; Widayanti, Tri (Vokasi: Jurnal Publikasi Ilmiah, 2023)
This research was conducted on the premise that the age of using lathes in the Mechanical Technology Laboratory of the Department of Mechanical Engineering Pontianak State Polytechnic has been more than 30 years since this Polytechnic was established. It is predicted that the resulting workpiece is not exactly sized by the tolerance limit given to students. This research was conducted by measuring geometry (geometric metrology) on lathes used by the Department of Mechanical Engineering students during machining practice. This study aims primarily to see whether there has been a significant deviation / beyond the allowable tolerance limit on the lathe used by students of the Pontianak State Polytechnic Mechanical Department, this research will later be able to take benefits that have to do with improving the skills of students of the Pontianak State Polytechnic Mechanical Engineering Department. Data obtained based on direct experiments on the object under study, the data obtained are processed with several analytical techniques by the variables studied, namely roundness analysis. The results showed that the tolerance of sphericity deviations in lathes MB 2 = 64 μm, can produce workpieces with tolerance values above 64 μm (IT 10). On lathes MB 2 = 84 μm, it can produce workpieces with tolerance values above 84μm (IT 10). Lathe MB 3 = 50 μm, can produce workpieces with tolerance values above 50 μm (IT 9). While the MB 4 lathe tolerance of the deviation of the roundness is 92 μm, it can produce workpieces with tolerance values above 92 μm (IT 11). While the lathe MB 5 tolerance of the deviation of roundness is 80 μm (IT 10), it can produce workpieces with tolerance values above 80 μm. Because these machines are still used for education, especially the implementation of practicum in machining process courses and production activities, improvements should be made to improve their performance.